Normal Baru dalam Praktik Keagamaan Islam pada Masa Pendemi di Kota Padang - Firma, Tri Bunga (Al-Adyan: Journal of Religious Studies, 2020)
The Coronavirus Disease 2019 (Covid-19) hitting the world has impacted all aspects of life, such as economy, social, tourism, education and religion. This study examines new habits in Muslim religious practices due to the pandemic in Padang City. As an area that contributes to the most covid-19 patients in Indonesia, which in fact the majority are Muslim, it has also experienced the impact of the coronavirus in religious life. Worship practices have also changed due to the outbreak. Mosques are closing down and worship services are beginning to be diverted to their respective homes. Such conditions require Muslims to rise up and must be able to be resilient. This is what encourages the birth of a new pattern of life (New Normal) so that the level of Muslim religious life returns to normal. New Normal requires Muslims to adapt and transform new habits (new habitus) in performing religious practices (prayer). For example, there is a distance shof, wearing a mask, carrying a prayer mat and other equipment needed when praying at the mosque, preparing hand sanitizers in every house of worship, and regularly checking the temperature of congregants visiting the mosque and always referring to health protocols that are guided by Maqosid Assyariah. On the other hand, the application (new normal) of worship, in practice, has been misunderstood by a number of Muslims in Padang city. It has triggered the birth of a new narrative that invites pros and cons, in the form of acceptance and rejection. Therefore, in this case, it is necessary to apply the principles of maqashid syari'ah amid Covid-19.Coronavirus Disease 2019 (Covid-19) yang melanda dunia telah berdampak pada semua aspek kehidupan, seperti ekonomi, sosial, pariwisata, pendidikan dan agama.  Studi ini mengkaji kebiasaan baru dalam praktik keagamaan Muslim akibat pandemi di Kota Padang. Sebagai daerah yang menyumbang pasien covid-19 terbanyak di Indonesia, yang mayoritas beragama Islam, juga mengalami dampak virus corona dalam kehidupan beragama.  Praktik ibadah juga telah berubah karena wabah tersebut. Masjid ditutup dan layanan ibadah mulai dialihkan ke rumah masing-masing. Kondisi seperti itu menuntut umat Islam untuk bangkit dan harus bisa kembali seperti normal.  Hal inilah yang mendorong lahirnya pola hidup baru (New Normal; Kenormalan baru) sehingga taraf kehidupan beragama umat Islam kembali seperti biasa. Kenormalan baru mewajibkan umat Islam untuk menyesuaikan dan mengubah kebiasaan baru (habitus baru) dalam menjalankan amalan keagamaan (sholat). Misalnya ada jarak shof, memakai masker, membawa sajadah dan perlengkapan lain yang dibutuhkan saat shalat di masjid, menyiapkan hand sanitizer di setiap rumah ibadah, serta rutin mengecek suhu jemaah yang berkunjung ke masjid dan selalu mengacu pada protokol kesehatan yang dipandu oleh Maqosid Assyariah.  Di sisi lain, penerapan (kenormalan baru) ibadah, dalam praktiknya, telah disalahartikan oleh sejumlah umat Islam di Kota Padang. Hal tersebut memicu lahirnya narasi baru yang mengundang pro dan kontra, berupa penerimaan dan penolakan.  Oleh karena itu, dalam hal ini, perlu diterapkan prinsip maqashid syari'ah di tengah pandemi.